2021
DOI: 10.3389/fbioe.2021.622835
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Trait Matching and Prevalence of Nisin Tolerance Systems in Lactococus lactis

Abstract: Lactococcus lactis cheese starter cultures typically contain a mix of many strains and may include variants that produce and/or tolerate the antimicrobial bacteriocin nisin. Nisin is well-established as an effective agent against several undesirable Gram-positive bacteria in cheese and various other foods. In the current study, we have examined the effect of nisin on 710 individual L. lactis strains during milk fermentations. Changes in milk acidification profiles with and without nisin exposure, ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Previous comparative genome analysis of 43 L. lactis genomes identified a subset of four strains retaining nisFEG/nisI genes, without biosynthesis genes, but did not determine if these strains retained full immune capacity to nisin [ 62 ]. A gene-trait matching study of 710 individual L. lactis strains identified 59 strains that encoded nisRKFEG , without other biosynthetic machinery, and found that nisFEG always co-occurred with nisRK and imparted the ability to survive and acidify milk in the presence a 1.5 µg·mL −1 level of nisin, but was not as effective as the presence of nsr [ 63 ]. The same study identified the presence of the nisin immunity protein-encoding gene nisI co-localised with nisP in 16/710 genomes, which conferred some degree of nisin resistance [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous comparative genome analysis of 43 L. lactis genomes identified a subset of four strains retaining nisFEG/nisI genes, without biosynthesis genes, but did not determine if these strains retained full immune capacity to nisin [ 62 ]. A gene-trait matching study of 710 individual L. lactis strains identified 59 strains that encoded nisRKFEG , without other biosynthetic machinery, and found that nisFEG always co-occurred with nisRK and imparted the ability to survive and acidify milk in the presence a 1.5 µg·mL −1 level of nisin, but was not as effective as the presence of nsr [ 63 ]. The same study identified the presence of the nisin immunity protein-encoding gene nisI co-localised with nisP in 16/710 genomes, which conferred some degree of nisin resistance [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A gene-trait matching study of 710 individual L. lactis strains identified 59 strains that encoded nisRKFEG , without other biosynthetic machinery, and found that nisFEG always co-occurred with nisRK and imparted the ability to survive and acidify milk in the presence a 1.5 µg·mL −1 level of nisin, but was not as effective as the presence of nsr [ 63 ]. The same study identified the presence of the nisin immunity protein-encoding gene nisI co-localised with nisP in 16/710 genomes, which conferred some degree of nisin resistance [ 63 ]. The nisIP sub-gene cluster was not detected among S. equinus genomes, which could result from the fact that the two genes are at opposing ends of the nisin E gene cluster, rather than co-localised, as they are in the nisin A gene cluster, which would more easily facilitate co-retention after the loss of other genes ( Figure 2 a).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that these genes are often positioned on transmissible elements such as plasmids (Froseth and McKay 1991 , Liu et al 1997 ), highlighting the potential for NSR-associated resistance transfer to other microbes. Indeed, the prevalence of NSR amongst lactococci was recently emphasized when whole genome sequencing of 710 dairy-associated L. lactis strains found that an impressive 270 (38%) harboured an nsr gene (van Gijtenbeek et al 2021 ). Furthermore, a singular nis I immunity gene located on a 50-kb plasmid was shown to provide nisin resistance to the non-nisin producer L. lactis NCDO712 (Tarazanova et al 2016 ).…”
Section: Nisin Resistance and Immunity Mechanismsmentioning
confidence: 99%
“…For instance, the MntH manganese transporter in Lacticaseibacillus rhamnosus and Lacticaseibacillus paracasei was established as a major factor responsible for the phenotype of yeast and mold inhibition (Siedler et al 2020 ), and BLAST -based identification of the encoding gene in other related species could subsequently be correlated with the inhibitory phenotype. Similarly, phenotypes such as nisin resistance (van Gijtenbeek et al 2021 ) or the ability to catabolize plant sugars in Lactococcus lactis (Siezen et al 2008 ) and polysaccharide synthesis in Oenococcus oeni (Dimopoulou et al 2016 ) were predicted through BLAST -based homology search.…”
Section: Knowledge-driven Approachesmentioning
confidence: 99%